Impact investment for urban cultural heritage. (September 2021) - Medda, Francesca; Lipparini, Fiorenza
Abstract: Impact investing is an emerging but fast fast-growing field in the financial industry. Urban cultural heritage investments having tangible and intangible features are often found in the asset allocation of impact investment portfolios. In this paper we map out the different financial mechanisms of impact investment in the heritage and creative sector and provide comprehensive coverage of several case studies. We assert that cultural heritage is likely to render different impacts and financial returns, so it is important to choose the appropriate investment mechanisms for financing cultural heritage. From this perspective, we present the structure of an impact investment fund dedicated to urban cultural heritage, adopting a portfolio approach to combine different types of capital and to support creative place-making at city or regional level. Highlights: Impact investing has the potential to support cultural heritage investments. Cities are prospering as hubs of economic opportunity and engines of national growth. Adopting a portfolio approach promotes creative place-making at city-regional level. Impact investments to facilitate a symbiotic approach; align public-private interests. Funding cultural infrastructures, while providing debt capital to creative industries.